FunTax Learning: Edukasi Pajak Interaktif Melalui Video Animasi - Kartika Ayu Kinanti; Yulian Ade Chandra; Marsuhin Marsuhin (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
The FunTax Learning Program: Interactive Tax Education through Animated Videos is a community service initiative aimed at improving tax literacy among students and young people. Low levels of tax understanding are largely caused by the technical nature of tax materials and their limited adaptation to the learning characteristics of the digital generation. This condition highlights the need for more communicative and engaging educational media innovations. The program was implemented through the development of educational animated videos based on visual learning approaches. The activity stages included tax material planning, simple script writing, animated video production by students, and dissemination through social media platforms. This approach was designed to simplify basic tax concepts using clear academic language supported by easily understood visual elements. The results indicate the availability of animated video-based tax education media that can be widely utilized as alternative learning resources. The FunTax Learning Program confirms that integrating digital technology into community service activities is effective in enhancing early tax understanding and awareness, while also contributing to the sustainable strengthening of public tax literacy